A systematic review on the effects of maternal calcium supplementation on offspring′s blood pressure - Fahimeh Jamshidi; Roya Kelishadi (Journal of Research in Medical Sciences, 2015)
Background: Evidence proposes that maternal calcium (Ca) supplement during pregnancy may be inversely associated with the off spring′s blood pressure (BP) level. It is suggested that increased maternal Ca intake during pregnancy may result in lower BP in the off spring. The reduction in the incidence of hypertension in mothers is documented but the effects on the off spring are uncertain. Materials and Methods: We conducted a systematic review of the literature to summarize the evidence supporting an association between maternal dietary Ca intake during pregnancy and the BP in the off spring. In this systematic review, relevant papers were selected in three phases. After quality assessment, a reviewer extracted the data while the other one checked the extracted data. We summarized the information regarding the association of maternal Ca intake either by food or supplements with BP in the off spring. Results: Four randomized trials and three observational studies were included in this review. The results were more consistent among the studies including older children (1-9 years) where a higher maternal Ca intake was associated with a reduction in the off spring′s systolic BP. One large randomized trial found a clinically and statistically significant reduction in the incidence of elevated BP in 7-year-old children [relative risk (RR) = 0.59, 95% confidence interval (CI) 0.39-0.90]. Conclusion: Overall, our findings confirm the beneficial effects of maternal Ca intake during pregnancy for the off spring′s BP level.